Comparative Characteristics Of Body Composition In Obesity Phenotypes - Rano K.Dadabaeva; Elnora A.Abduganieva; Kenesh O.Djusupov; Indrani Kalkan; Oybek F.Eshmamatov (Zien Journals, 2025)
to study bioimpedance parameters of Uzbek women of childbearing age suffering from metabolically healthy and metabolically complicated obesity, to study their correlation with the degree of obesity and some biological markers
Keywords: markers; parameters; obesity; childbearing